Governing Carbon Dioxide Removal in the UK: Lessons Learned and Challenges Ahead - Lezaun, Javier; Healey, Peter; Kruger, Tim; Smith, Stephen M. (Frontiers in Climate, 2021)
This Policy Brief reviews the experience of the UK in developing principles for the governance of carbon dioxide removal (CDR) at scale. Early discussions on CDR governance took place in two separate and somewhat disjointed policy domains: forestry, on the one hand, and R&D support for novel “geoengineering” technologies, on the other. The adoption by the UK government of a 2050 “net zero” target is forcing an integration of these disparate perspectives, and should lead to a more explicit articulation of the role CDR is expected to play in UK climate strategy. This need for clarification is revealing some of underlying tensions and divisions in public views on CDR, particularly when it comes to forms of capture and sequestration deemed to be “non-natural.” We propose some principles to ensure that the development and deployment of carbon dioxide removal at scale strengthens a commitment to ambitious climate change mitigation and can thus enjoy broad public support.